Annual reviews of computational physics - edited by Dietrich Stauffer
The sixth volume of the series covers topics ranging from the generation of good random numbers to statistical physics, quantum mechanics, quantum computers and polymers, to protein folding and immunology simulations. It should thus be of interest not only to computational physicists but also to experts in computer science as well as theoretical biology